The Level of Knowledge of Jatimulya Bekasi Village Residents on the Use of Vitamin D during the Covid 19 Pandemic and According to Islamic Overview - Syaffira Novitasari Nadilla; Dharma Permana; Andri Gunawan (Junior Medical Journal, 2023)
The world is facing the Covid-19 pandemic, where the body is very susceptible to disease so, it requires increasing body resistance by increasing intake of vitamins, especially vitamin D (Nainggolan, 2020). Vitamin D is a pro-hormone that helps absorb calcium and boosts the immune system. Therefore, to prevent the negative effects arising from a deficiency or excess of vitamin D in the body, good knowledge is needed on the use of vitamin D. This research is to analyze level of knowledge of the residents RT 001 and RT 002 Jatimulya Bekasi regarding the use of vitamin D during the Covid-19 pandemic and to know the importance of seeking knowledge and maintaining health in Islam. This type of research is descriptive correlative and cross-sectional research design with the population studied being residents of RT 001 and RT 002, Jatimulya Bekasi Village, aged 17-55 years. The sample studied was 123 respondents with simple random sampling. This research method is univariate and bivariate analysis. The results showed that majority of people with good knowledge of use vitamin D were 63 people (51.2%). The statistic results among the factors of age, education, and work had no effect with a p-value 0.05 on the level of knowledge on the use of vitamin D. In the Qur'an seeking knowledge and maintaining health which is a sign of the greatness of Allah SWT is an obligation.